Enhancement of nutritive value of palm kernel cake by solid state fermentation with Lactobacillus plantarum - Murad, N. Z.; Abdullah, Norhani; Foo, H. L. (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Palm kernel cake (PKC) is an abundant by-product from the palm oil industry in Malaysia. However, the usage of PKC is limited in poultry diets mainly due to its high fiber content that contributes to the low digestibility. Therefore, PKC has to be treated by using chemical or biological methods to reduce the fibre content. In the present study, PKC was biologically treated by solid state fermentation (SSF) with Lactobacillus plantarumas a means to improve the nutritive value of PKC. The SSF was optimised by using response surface methodology (RSM) with bacterial inoculation level, moisture content and incubation time as the independent variables. According to RSM results, the optimised conditions obtained for SSF were 0.2% inoculation level (1011 colony forming units/g PKC), 40% moisture and incubation period of 10 days. The results showed that SSF with L. plantarum significantly (P<0.05) reduced the CF and NDF content of PKC. Significant (P<0.05) increases in reducing sugar and mannose were also observed at 10 days of fermentation. The amount of reducing sugar increased to 21.23mg/g compared to untreated PKC which was 14.57 mg/g. The amount of mannose increased to 0.46 mg/gfrom0.29 mg/g. Hence, the nutritive value of PKC could be improved by SSF with L. plantarum.